Forest Fire Detection Using String Matching In The Satellite Imagery - Yuliana Kolyaan (International Conference on Engineering and Technology Development (ICETD), 2012)
Wildfires are still one of the problems that are difficult to overcome and into the spotlight of the world, especially those related to Global Warming or Global Warming. During this time, it can be resolved using conventional means, but it often happens that problems in the field of fire leads to delayed treatment. Seeing these conditions, it would require methods or the relatively more rapid manner. Forest Fire Detection Systems using String Matching on the satellite imagery particularly hotspot data can be used as one solution. System uses the Boyer-Moore String Matching Algorithm on the image or images of satellite imagery by selecting a color image, convert image forms the string, and then performed a search with string.Sistem way pattern matching can provide output in the form of a warning if there are differences in the pattern string is found and exceeds the tolerance is understood as an indication of a fire on the specific forest area being processed.